2009
DOI: 10.1097/01.aoa.0000350632.42302.43
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Hypofunction and Pregnancy Outcome

Abstract: OBJECTIVE-To estimate whether maternal thyroid hypofunction is associated with complications. METHODS-A total of 10,990 patients had first-and second-trimester serum assayed for thyroid-stimulating hormone (TSH), free thyroxine (freeT4), and antithyroglobulin and antithyroid peroxidase antibodies. Thyroid hypofunction was defined as 1) subclinical hypothyroidism: TSH levels above the 97.5th percentile and free T4 between the 2.5th and 97.5th percentiles or 2) hypothyroxinemia: TSH between the 2.5th and 97.5th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 17 publications
4
58
2
4
Order By: Relevance
“…In some studies, preterm delivery has been found to be 3-fold more common in hypothyroid pregnant women and has also been associated with an increase in spontaneous abortions, [52][53][54] although no adverse outcomes were found in a very large study of mild (subclinical) disease. 55 Another worrying danger associated with maternal hypothyroxinemia (especially when present during the first trimester) is the adverse consequences to child neuropsychointellectual development, as has been demonstrated by several studies 6,16,25,56,57 (Table 3). Whether very mild hypothyroidism has the same associations remains uncertain.…”
mentioning
confidence: 96%
“…In some studies, preterm delivery has been found to be 3-fold more common in hypothyroid pregnant women and has also been associated with an increase in spontaneous abortions, [52][53][54] although no adverse outcomes were found in a very large study of mild (subclinical) disease. 55 Another worrying danger associated with maternal hypothyroxinemia (especially when present during the first trimester) is the adverse consequences to child neuropsychointellectual development, as has been demonstrated by several studies 6,16,25,56,57 (Table 3). Whether very mild hypothyroidism has the same associations remains uncertain.…”
mentioning
confidence: 96%
“…Furthermore, high TSH levels in women during pregnancy have been associated with an increased risk of neurocognitive deficits in the offspring (17). Other studies, however, have not found any adverse outcomes associated with SCH (18)(19)(20)(21). Moreover, there is uncertainty regarding the impact of levothyroxine replacement on improving outcomes in pregnant women with SCH (4).…”
mentioning
confidence: 99%
“…[8][9][10][11] However, the risks of these adverse outcomes are not increased among women with hypothyroxinemia in pregnancy. 12,13 These findings led several professional organizations to recommend routine prenatal screening for and treatment of subclinical thyroid disease during pregnancy. 14 This recommendation could affect more than 15% of pregnant women, depending on the thyrotropin and free T 4 thresholds used.…”
mentioning
confidence: 99%